Analisis Kepuasan Pasien Terhadap Kualitas Layanan Poli Gigi di Rumah Sakit Banyumanik Semarang - Aulia Ika Pratiwi; Bagoes Widjanarko; Sutopo Patria Jati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
Based on the medical records of the Banyumanik Hospital, the number of visits in the Banyumanik Hospital dental clinic in 2015 was 766 patients (90%), increasing in 2016 to 781 (91%), but decreased in 2017 to 724 patients (85%) one factor the cause is the quality of service. This study aimed to analyze the effect of quality outpatient services on patient satisfaction in dental polyclinics in hospitals. Banyumanik Semarang. This was quantitative research with cross sectional design. The number of samples in this study were 54 respondents. Research variables were 5 dimensions of service quality. The results of the study showed the dimensions of the quality of outpatient care in dental poly: Real Evidence had a poor result of 68.5, reliability had poor results of 32 respondents 59.3%, poor responsiveness 40.7%, poor guarantees 59.3%, poor empathy at 55.6%, and less patient satisfaction at 44.4%. In the results of multivariate analysis that the responsiveness variable has the highest significance of 0.039 with the value of Exp (B) 4,566. The conclusion of this study was that the dimensions of service quality namely Real Evidence, Responsiveness, and Empathy affect patient satisfaction, while the guarantee does not affect the satisfaction of outpatients in the Dental Polyclinic Hospital. Banyumanik Semarang.